الفلسفة النقدية عند محمّد مصايف - مليح, فايزة (جامعة الوادي - University of Eloued, 2017)
اعتمد الدّكتور محمّد مصايف على معايير واضحة أثناء ممارسته للنّقد، حيث نجده يركّز على الاعتدال في الحكم على النّص قيد الدّراسة، وعدم الخوض في تدنيس شخصية صاحب النّص . وهذا المنهج الفلسفي اتبعه كذلك في حياته اليومية. كما نجده يحدّد وظيفة النّقد من خلال تحديد الموضوع بالقراءة المتأنّية حتّى لا يخرج النّاقد عن النّص ثمّ يحدّد الهدف المرجو من هذا النّص This research would try to shed light on the methodology set by Mohammed Mesaif and that is so clear in applying critics on any given text. He based on a dimension of equilibrium in judging any critical text. He has always put the writer and his personality aside when criticizing his text. This method was inspired and practiced even in his daily life. He then was able to limit and explicit the critical function through the theme of the text dealt with and that by means of a so concentrated lecture and so sort out the objective of the text.
مقال
Keywords: الفلسفة النقدية ؛محمّد مصايف; Methodology – critics –equilibrum in judging – critical function.